2015
DOI: 10.1007/s00247-015-3404-y
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of childhood angiomatoid fibrous histiocytoma with pathological correlation

Abstract: The imaging detection of intralesional blood-filled cystic spaces with fluid-fluid levels, enhancing fibrous pseudocapsule and hemosiderin deposition in a soft-tissue tumor in a child may suggest the diagnosis of angiomatoid fibrous histiocytoma. A history of systemic symptoms and anemia in the presence of a soft-tissue mass may also be a clue for the diagnosis of angiomatoid fibrous histiocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…The onset age of the current case was similar to that of previously described cases [10]. Subcutaneous AFH in the iliac region is extremely rare.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The onset age of the current case was similar to that of previously described cases [10]. Subcutaneous AFH in the iliac region is extremely rare.…”
Section: Discussionsupporting
confidence: 85%
“…Some groups have reported MRI features of AFH, including cystic areas, pseudocapsules, edema of surrounding mass, enhancement, and fluid–fluid levels [1012], which were observed in the current case. Although the MRI features of AFH described in the literature may aid diagnosis [6, 13], none of them are considered to be significant [10]. The characteristic histological features of AFH have been well described [2].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Some groups have reported the MRI features of AFH, including cystic areas, pseudocapsules, peritumoral edema, enhancement, and fluid–fluid level [713]. On the basis of these findings, we evaluated the imaging characteristics of each case (Table 2, Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The pattern of gadolinium enhancement is a variegated internal and nodular peripheral appearance. In addition, some groups reported that AFH shows cystic areas, pseudocapsules, hemosiderin, and fluid–fluid levels on MRI [713]. Martinez et al reported the double rim sign and invasive pattern as novel MRI findings for AFH [15].…”
Section: Discussionmentioning
confidence: 99%